Further characterization of clinical and laboratory features in VEXAS syndrome: large‐scale analysis of a multicentre case series of 116 French patients. (1st March 2022) - Georgin‐Lavialle, S.; Terrier, B.; Guedon, A.F.; Heiblig, M.; Comont, T.; Lazaro, E.; Lacombe, V.; Terriou, L.; Ardois, S.; Bouaziz, J.‐D.; Mathian, A.; Le Guenno, G.; et al.
Summary: Background: A new autoinflammatory syndrome related to somatic mutations of UBA1 was recently described and called VEXAS syndrome ('Vacuoles, E1 Enzyme, X‐linked, Autoinflammatory, Somatic syndrome'). Objectives: To describe clinical characteristics, laboratory findings and outcomes of VEXAS syndrome. Methods: One hundred and sixteen patients with VEXAS syndrome were referred to a French multicentre registry between November 2020 and May 2021. The frequency and median of parameters and vital status, from diagnosis to the end of the follow‐up, were recorded. Results: The main clinical features of VEXAS syndrome were found to be skin lesions (83%), noninfectious fever (64%), weight loss (62%), lung involvement (50%), ocular symptoms (39%), relapsing chondritis (36%), venous thrombosis (35%), lymph nodes (34%) and arthralgia (27%). Haematological disease was present in 58 cases (50%): myelodysplastic syndrome (MDS; n = 58) and monoclonal gammopathy of unknown significance ( n = 12; all patients with MGUS also have a MDS). UBA1 mutations included p.M41T (45%), p.M41V (30%), p.M41L (18%) and splice mutations (7%). After a median follow‐up of 3 years, 18 patients died (15·5%; nine of infection and three due to MDS progression). Unsupervised analysis identified three clusters: cluster 1 (47%; mild‐to‐moderate disease); cluster 2 (16%; underlying MDS and higher mortality rates); and cluster 3 (37%; constitutional manifestations, higher C‐reactive protein levels and less frequent chondritis). The 5‐year probability of survival was 84·2% in cluster 1, 50·5% in cluster 2 and 89·6% in cluster 3. The UBA1 p.Met41Leu mutation was associated with a better prognosis. Conclusions: VEXAS syndrome has a large spectrum of organ manifestations and shows different clinical and prognostic profiles. It also raises a potential impact of the identified UBA1 mutation.